Physiological responses of hybrid grouper (Epinephelus fuscoguttatus X Epinephelus lanceolatus) to temperature fluctuation stress revealed by LCMS/MS-based mucus and sera metabolomics - Mujar, Ellia Kartini; Matusin, Saleema; Yahya, Nur Syahirah; Ahamad Bustamam, Muhammad Safwan; Christianus, Annie; Shaari, Khozirah; Kassim, Nur Kartinee; Abas, Faridah; Tan, Jen Kit; Ismail, Intan Safinar (Springer Science and Business Media B.V., 2025)
Aquaculture, which involves the cultivation of aquatic animals and plants, is recognised to be an effective and vital resource-efficient food production system for supplying affordable protein to humans. Hybrid grouper (Epinephelus fuscoguttatus x Epinephelus lanceolatus) is a marine carnivorous teleost that has a high economic importance in the marine aquaculture industry particularly in countries in the Asian region. However, the vulnerability of juvenile hybrid grouper to temperature fluctuations stemming from the acceleration of climate change is regarded as one of significant threats to their market supply and a major concern for the aquaculture industry. In the present study, LCMS/MS–based mucus and sera metabolomics were used to investigate the physiological responses of juvenile hybrid grouper via their behavioural response towards temperature fluctuation stress that could be translated as indicators for either resilience or susceptibility to the stressors. Susceptible fish exhibited pronounced behavioural responses, including cessation of feeding and erratic swimming. In contrast, resilient fish displayed relatively stable behaviour, comparable to control fish, with reduced feeding as a primary deviation. A total of 36 mucus metabolites (VIP > 1) were profiled in OPLSDA in juvenile hybrid grouper subjected to temperature fluctuation stress. Among these, 20 and 16 metabolites were significantly altered (Student’s t-test, p < 0.05) in susceptible (MSG) and resilient (MRG) fish in comparison to the control (CG), respectively. Although OPLSDA did not reveal a clear separation between the two groups, 4 metabolites namely glycerophosphocholine, N-acetylgalactosamine, N-acetylglucosamine, and pantothenic acid differed significantly between them. In sera, 54 metabolites (VIP > 1) were profiled, with 38 and 26 significantly altered in the susceptible (SSG) and resilient (SRG) groups, respectively. Comparative analysis between significant and resilient groups resulted in the nomination of hypoxanthine, guanosine, guanine, methionine, DL-malic acid, and glucose as potential biomarkers for susceptibility in juvenile hybrid grouper. Pathway analysis of these metabolite markers revealed that temperature stress mainly affected purine metabolism, TCA cycle, cysteine and methionine metabolism, and pyruvate metabolism. Overall, the findings of this study provide insights into the physiological regulation of juvenile hybrid grouper that are susceptible to temperature changes through their behavioural response, as well as a framework for future research.